SVT 1re : Sciences de la Vie et de la Terre : programme 2019 - Amilhat, Aude; Augeray, Philippe; Barthélémy, Raphaëlle; Brunet, Philippe; Coupel-Clauce, Hélène, 1972-; Fouquet, Carole; Koch, Eve; Lieury, Alice; Jomard, Sandrine; Pasco, Ariane; Samuel, Julien (Magnard, 2019)
Un manuel de sciences de la vie et de la terre pour accompagner les élèves de première. ↑Electre 2019